Tunable frequency diode laser system for spectroscopy applications - Altuna, Gabriel (2014)
In this work, we describe a practical and simple system to control the operation of a diode laser in a specific frequency using an external optical cavity. We show that fixing the current and temperature, the laser can oscillate selectively at different frequencies by controlling the longitude of the external cavity. This system laser was used with success in an experiment of absorption saturated spectroscopy at the line D2 of cesium.